Mere Gifting: Liking a Gift More Because It Is Shared. (November 2017) - Polman, Evan; Maglio, Sam J.
We investigated a type of mere similarity that describes owning the same item as someone else. Moreover, we examined this mere similarity in a gift-giving context, whereby givers gift something that they also buy for themselves (a behavior we call "companionizing"). Using a Heiderian account of balancing unit-sentiment relations, we tested whether gift recipients like gifts more when gifts are companionized. Akin to mere ownership, which describes people liking their possessions more merely because they own them, we tested a complementary prediction: whether people like their possessions more merely because others own them too. Thus, in a departure from previous work, we examined a type of similarity based on two people sharing the same material item. We find that this type of sharing causes gift recipients to like their gifts more, and feel closer to gift givers.